Exploring the perceptions of community members on contributing factors to rape in selected Mankweng Communities - Mamabolo, Sekwaila Naum (My University, 2022)
This study was conducted to explore the perceptions of community members on contributing factors of rape in the selected Mankweng communities, namely: Mentz, Ga-Makanye and Ga-Thoka, following a qualitative research approach, with an exploratory research design. The non-probability sampling: Purposive sampling was adopted to sample 30 participants. Three Focus Groups Discussions (FGDs), consisting of 10 individuals formed part of this study and the Thematic Content Analysis (TCA) was used for analysis. The consulted seminal studies were reviewed and coupled with the Differential Risk Model as the adopted theoretical framework, in order to identify different categories that would explain the contributing factors of rape in the selected study locations. From the studies on this subject and information gathered from the selected participants; four (04) major contributing factors to rape in the Mankweng selected areas emerged, demarcated as follows; 1) Structural factors which include men that are raised in families with strong patriarchal structures which are more likely to become violent and force themselves on women because they feel superior to women, 2) Socio-cultural factors which entail the societies that normalise women being violated and rape because they believe that women are inferior to men and should be submissive, 3) Psychological factors consist of all the effects that both the victims and the community endure due to the crime committed; and lastly, 4) Economic factors explain how women are exposed to chances of being raped because of material gains in exchange for sexual favors. This study recommends that youth in the selected communities should be trained to become peer educators to learn more about rape, understand the associated effects/ impacts on society and potential victims, and programmes should be hosted within these communities to alert residents about the scourge of rape. The study further recommends that the police officials change their attitudes towards the community members and work with them in preventing rape from occurring.
Thesis (M. A. (Criminology and Criminal Justice)) -- University of Limpopo, 2021
Keywords: Community members; Contributing factors; Exploring; Mankweng communities; Perceptions; Rape; Rape victims -- Services for -- South Africa; Sexually abused children -- South Africa; Anti-rape movement